Sony Labou Tansi, afflux des écrits et flux de l’écriture - Nicolas Martin-Granel (Continents manuscrits)
This appraisal of archives left by Sony Labou Tansi consists of two parts. The first one appears as a history of maintenance and of promotion of Tansi’s writings, which are an immense and unknown land. Their eventful history starts, where the literary production ends: upon the death of Sony Labou Tansi in 1995. Physically, the writings are put down in schoolchild notebooks, thrown as they came at the bottom of a little library at the author’s house of Makélékélé in Brazzaville. With no date, sometimes with no title on them, these notebooks appear as a real challenge for genetic critic, who is trying to class them, to make up their stocklist, to scan and to publish them. Reconstructing their history through multiple versions and successive transformations ends up with tracing a map of a textual labyrinth consisting not only of literary production of Sony Labou Tansi, broken up between France and the Congo, but also on notebooks and letters given by the author to the crowd of his friend readers and his publishers. In the second part of the article, we set out to retrace the creative process, to reconstruct the vitalist and hypertextual logic of Tansi’s writing. If Sony Labou Tansi used to write as you breath, his writing with its improvised aspect, described by the genetic criticism as « à processus », comes, from anthropological point of view, close to the scriptural prediction: a speech-writing in continuous progression – against the progress; never turning back towards reading.